Theological Anthropocentrism: An Interpretation of Scripture and Semitic Theodicy in Overcoming the Environmental Crisis - Nurul Huda; Arqom Kuswanjono; Agus Himmawan Utomo (Universitas Negeri Jakarta, 2023)
This research aims to explore by offering theodicy as the basis for anthropocentric theology to purify God of all the bad images that occur creation of God, and theological criticism of the theocentric view which positions God with his absolute will to do anything, including creating and allowing environmental crises to occur also the anthropocentric opinion which positions humans with their free will has led to an environmental crisis. The contradiction of belief in God as the Most Perfect Essence with the fact that there is a problem of evil (imperfection) in creation of God that a perennial debate that has existed since the birth of these religions. These research method uses a literature review and data analysis using a qualitative hermentic approach. The results of the study describe the views of the Bible and the Qur'an about human freedom and present theodicy debates from traditional to modern in Christian and Islamic theology, about the role and ethics of humans towards nature or the environments. The results of the research are hoped it will become theological literacy or provide theological arguments for the need for human intervention to be fair, good, and true to the environment. Apart from being an implementation of faith in the Supreme Being, this intervention is also a human responsibility as a moral agent for protecting the environment.